Strategi pengelolaan taman median jalan di Kota Pekanbaru - Angga Paskibragustian; Thamrin Thamrin; Sri Wulandari (Jurnal Zona, 2020)
Research with the aim of making an inventory of various types of plants, management, maintenance, monitoring, monitoring of road users and formulating a road park management strategy in Pekanbaru City was carried out in January 2020. The research location was in 21 Median Park Road in Pekanbaru City. Descriptive research approach with observation method. The research sample was determined by 3 daily freelance officers / median park road. and 5 road users per road in Jalan Median Park as well as interviews with the Pekanbaru City Parks and Cleanliness Service Staff. The collected data will be presented in a narrative and discussed descriptively. The road median park management strategy in Pekanbaru City was prepared using a SWOT analysis. The results showed that the inventory of plant species diversity in road median parks in Pekanbaru City were Aglonena, Bougenville, Ornamental Banana, Daffodil, Red Soka, Batavia, Oleander, Mawar, Tongue-in-Law, Ketapang Kencana, Palem, Angsana, Bintan, Pulai, Tanjung, Butterfly Tree, Azahra Plant, Japanese Bamboo, Tasbih Flower, Drasena, Yellow Pruning, Ornamental Pineapple, Landep, Tapak Dara, Paris Lilies, Spinach, White Taiwan, Brazilian Lilies, Blood Symbols, Iris, Lantana, White Lilies, Bombay Sutra, Adam Eve, Ruelia Purple Flower. Landscape management (planning, maintenance) of road median parks in Pekanbaru City still has not followed the established SOP. The perception of road users towards the road median park in Pekanbaru City is good, but there are still plants that must be maintained by the relevant Agency. The road median park management strategy in Pekanbaru City is to urge schools in Pekanbaru City to take part in the management of the median park road, involve business and industry players in managing road median parks, planting croton plants that function as aesthetics and absorb pollutants, improve facilities and infrastructure in the road median park, Providing socialization to the community about the importance of preserving the road median park, Providing counseling to casual daily officers regarding the function of the road median park.